2000
DOI: 10.1111/j.1574-6968.2000.tb09071.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of theNeurospora crassaheat shock factor with the heat shock element during heat shock and different developmental stages

Abstract: The interaction of the heat shock factor (HSF) with the heat shock element (HSE) was determined by a non-radioactive electrophoretic mobility shift assay, in order to analyze HSF regulation in Neurospora crassa. HSF binds to HSE under normal, non-stress conditions and is thus constitutively trimerized. Upon heat shock, the HSF-HSE complex shows a retarded mobility. This was also observed in Saccharomyces cerevisiae, where this mobility shift was shown to be due to HSF phosphorylation [Sorger and Pelham (1988) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, small HSPs, such as HSP26 and HSP42, play a vital role in promoting protein solubility when HS leads to general cytosolic protein unfolding (21). In most fungi, the increased expression of HSPs in a stressed cell is mediated primarily by heat shock factors (HSFs) (22).…”
mentioning
confidence: 99%
“…Furthermore, small HSPs, such as HSP26 and HSP42, play a vital role in promoting protein solubility when HS leads to general cytosolic protein unfolding (21). In most fungi, the increased expression of HSPs in a stressed cell is mediated primarily by heat shock factors (HSFs) (22).…”
mentioning
confidence: 99%
“…Despite the lack of nucleotide-resolution studies characterizing these hse as functional, their sequence identity strongly suggests that these regions are conserved and are likely recognized by HSFs, commanded by the major regulator in Neurospora: HSF-1 (NCU08512). In addition, it has been shown that the HSF of Neurospora can efficiently recognize a hse from yeast [81]. Based on this, we used one of the HSF-1 motifs obtained from yeast and N. crassa to further identify new, and confirm the previously proposed hse in the hsp30 promoter (Tabla S2, S3).…”
Section: Discussionmentioning
confidence: 74%
“…Despite the lack of nucleotide resolution studies characterizing these hse as functional, their sequence identity strongly suggests that these regions are conserved and are likely recognized by HSFs, commanded by the major regulator in Neurospora , HSF-1 (NCU08512). In addition, it has been shown that the HSF of Neurospora can efficiently recognize an hse from yeast ( 81 ). Based on this, we used one of the HSF-1 motifs obtained from yeast and N. crassa to further identify new hse and confirm the previously proposed hse in the hsp30 promoter (Table S1 at https://doi.org/10.6084/m9.figshare.21774671 and Table S2 at https://doi.org/10.6084/m9.figshare.21774632 ).…”
Section: Discussionmentioning
confidence: 99%